Computer Assisted Instruction as a Media for Understanding Cultural Diversity - Bambang Dibyo Wiyono; Duwi Vebiana (Bisma The Journal of Counseling, 2022)
Computer Assisted Instruction as media for Understanding Cultural Diversity contains the cultural diversity concept in Indonesia, equipped with interesting video and animation that can easily understand by student. The purpose of the research  is to produce Computer Assisted Instruction as a computer-based that meet the acceptability criteria. This research use Borg&Gall development model. The results of the qualitative assessment of 2 material and media expert and potential user the result were 90.15% from media experts, 89,6% from material experts and 89.17% from potential users all of the result have criteria “very good, no need to be revised”. Based the results of the quantitative assessment, it can be concluded that Computer Assisted Instruction and Media of Cultural Understanding as media for understanding cultural diversity for students meets the acceptability criteria.